2017
DOI: 10.3346/jkms.2017.32.8.1295
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Follow-up Courses after Discharge from Neonatal Intensive Care Unit between Very Low Birth Weight Infants with and without Home Oxygen

Abstract: In order to investigate the clinical impact of home oxygen use for care of premature infants, we compared the follow-up courses after neonatal intensive care unit (NICU) discharge between very low birth weight infants (VLBWIs) with and without home oxygen. We retrospectively identified 1,232 VLBWIs born at 22 to 32 weeks of gestation, discharged from the NICU of 43 hospitals in Korea between April 2009 and March 2010, and followed them up until April 2011. Clinical outcomes, medical service uses, and readmissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…Our study showed that the duration of home oxygen use was 25 (7,42) days, which is shorter than previous studies (20,27). Kim et al reported that the duration of home oxygen was 69 ± 99 days for very low birth weight infants; however, Ejiawoko et al showed that the median age of weaning off supplemental oxygen was 10.1 months after initial hospital discharge.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Our study showed that the duration of home oxygen use was 25 (7,42) days, which is shorter than previous studies (20,27). Kim et al reported that the duration of home oxygen was 69 ± 99 days for very low birth weight infants; however, Ejiawoko et al showed that the median age of weaning off supplemental oxygen was 10.1 months after initial hospital discharge.…”
Section: Discussioncontrasting
confidence: 59%
“…Lagatta et al (26) reported that home oxygen was used in 53% of infants in 22 regional NICUs in the United States. Kim et al (27) found that the proportion of home oxygen was 13.7% in total VLBW infants and 54.6% in GA less than 29 weeks. Our single-center data showed that about one-third of infants with BPD needed home oxygen post-discharge.…”
Section: Discussionmentioning
confidence: 99%
“…BPD is the most common chronic disease in VLBW infants (Hack et al, ) and is associated with non‐respiratory complications such as cerebral palsy and other movement disorders, cognitive impairment, and major sensory disturbances in hearing and vision (Cheong & Doyle, ; Majnemer et al, ). Respiratory problems are the most common causes of hospital readmission 1 year after discharge among VLBW infants (Kim et al, ; Ralser et al, ; Vohr et al, ). In this study, respiratory diseases such as RDS or BPD were the most worrisome problems and important concern of parents of premature infants.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, respiratory diseases such as RDS or BPD were the most worrisome problems and important concern of parents of premature infants. In preterm infants who needed oxygen at discharge, hospital utilization, reentry, and mortality rates were high regardless of gestational age (Kim et al, ). Therefore, medical staff needs to provide parents with detailed and accurate information concerning respiratory distress, even if the premature infants do not have acute respiratory illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…1 Medical advancements within the neonatal intensive care unit (NICU) over the past 2 decades have increased the survival of premature infants both within the United States [2][3][4][5] and internationally, 6,7 especially for those born extremely preterm (ie, <28 weeks' gestation). 2 The increase in preterm birth and survival has resulted in a growing population of children with prematurity-related morbidities, such as technology-dependent infants discharged from the NICU who require continued respiratory [8][9][10][11][12] and/or nutritional [13][14][15][16] support at home. Medical technologies enable infants to continue to grow and thrive at home following NICU discharge.…”
mentioning
confidence: 99%